2002
DOI: 10.1007/bf03326428
|View full text |Cite
|
Sign up to set email alerts
|

IL18 polymorphism is associated with an increased risk of Crohn’s disease

Abstract: IL18 is probably one of several genes that determine susceptibility to Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 29 publications
1
49
3
Order By: Relevance
“…SNP rs360719A>G (À1297) is at the OCT-1 binding site [29], rs1946518T>G (À607) at a potential cyclic adenosine monophosphate (c-AMP)-responsive element-binding site [10], and rs187238G>C (À137) at a H4TF-1 nuclear factor binding site [10]. These SNPs have been reported to be individually or jointly associated with susceptibility to Crohn disease [30], inflammatory bowel disease [31], type 1 diabetes mellitus [11][12][13], renal manifestations [32] or arthritis in SLE [33], presence of anti-GAD antibody in Graves disease [34], or asthma [35,36]. However, rs1946518 alone is not associated with various autoimmune diseases including type 1 diabetes, rheumatoid arthritis, systemic lupus erythematosus, Crohn disease and ulcerative colitis in a metaanalysis [37] or with autoimmune thyroid disease [38] or Graves disease [34,39] in other individual studies, nor with HT, in our study.…”
Section: Discussionmentioning
confidence: 97%
“…SNP rs360719A>G (À1297) is at the OCT-1 binding site [29], rs1946518T>G (À607) at a potential cyclic adenosine monophosphate (c-AMP)-responsive element-binding site [10], and rs187238G>C (À137) at a H4TF-1 nuclear factor binding site [10]. These SNPs have been reported to be individually or jointly associated with susceptibility to Crohn disease [30], inflammatory bowel disease [31], type 1 diabetes mellitus [11][12][13], renal manifestations [32] or arthritis in SLE [33], presence of anti-GAD antibody in Graves disease [34], or asthma [35,36]. However, rs1946518 alone is not associated with various autoimmune diseases including type 1 diabetes, rheumatoid arthritis, systemic lupus erythematosus, Crohn disease and ulcerative colitis in a metaanalysis [37] or with autoimmune thyroid disease [38] or Graves disease [34,39] in other individual studies, nor with HT, in our study.…”
Section: Discussionmentioning
confidence: 97%
“…This model has also been used to analyze colitisassociated colorectal cancer [38]. IL-1b and IL-18 have key roles in inducing colorectal tumor formation [39][40][41]. One carcinogenic mechanism of this AOM/DSS model may be that IL-1b induced by neutrophils leads to macrophage production of IL-6, as a tumor promoter [42].…”
Section: Gut Microbiota and Experimental Models Of Ibdmentioning
confidence: 99%
“…In CD, no significant differences were observed at positions –607 and –137 in this study and in a Japanese one [34]. However, it has been reported that a silent allelic variant in the coding region of IL-18 was associated with CD [35]. We also searched p-ANCA and ASCA antibodies in IBD patients and observed 26% of positivity for p-ANCA in UC patients and 8% in CD patients.…”
Section: Discussionmentioning
confidence: 89%